2007
DOI: 10.1302/0301-620x.89b2.17754
|View full text |Cite
|
Sign up to set email alerts
|

Repair of osteochondral defects with a new porous synthetic polymer scaffold

Abstract: We developed a new porous scaffold made from a synthetic polymer, poly(DL-lactide-co-glycolide) (PLG), and evaluated its use in the repair of cartilage. Osteochondral defects made on the femoral trochlear of rabbits were treated by transplantation of the PLG scaffold, examined histologically and compared with an untreated control group. Fibrous tissue was initially organised in an arcade array with poor cellularity at the articular surface of the scaffold. The tissue regenerated to cartilage at the articular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 18 publications
0
28
0
4
Order By: Relevance
“…This would lead to regeneration of cartilage and bone while the PLG scaffold is absorbed. 9,10 In this study, new bone formation was observed in the deep zone of the scaffold at postoperative week 3, and this new bone formation was directly connected to the surrounding bone trabeculae. Because chondrocytes were not observed in the deep zone of the scaffold prior to the direct bone ingrowth, the process of bone ingrowth might be independent of the endochondral ossification sequence.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…This would lead to regeneration of cartilage and bone while the PLG scaffold is absorbed. 9,10 In this study, new bone formation was observed in the deep zone of the scaffold at postoperative week 3, and this new bone formation was directly connected to the surrounding bone trabeculae. Because chondrocytes were not observed in the deep zone of the scaffold prior to the direct bone ingrowth, the process of bone ingrowth might be independent of the endochondral ossification sequence.…”
Section: Discussionmentioning
confidence: 59%
“…[5][6][7][8] We have reported that a bioabsorbable synthetic polymer scaffold made of poly(DL-lactide-co-glycolide) (PLG) can repair osteochondral defects in a rabbit model. 9,10 This bioabsorbable scaffold has the capacity to repair full-thickness osteochondral defects of a critical size without using cultured cells. The efficacy of the scaffold is due to the structural support that it provides and its ability to hold mesenchymal stem cells that erupt from the bone marrow.…”
mentioning
confidence: 99%
“…In repairing the full-thickness osteochondral defect, exogenous cells may not be required because bone marrow cells erupted from the bottom of the osteochondral defect have a potential to differentiate to cartilage and bone, when the osteochondral defect was treated with the optimal scaffold combined with several factors: multiphasic bioabsorbable scaffold containing both the region for bone repairing and the region for cartilage repairing [5], amorphous calcium phosphate/poly (L-lactic acid) combined with fibroblast growth factor [8], hyaluronan-and polyesterbased scaffolds [17], a composite of interconnected porous hydroxyapatite and synthetic polymer combined with bone morphogenetic protein-2 [18] and synthetic PLG scaffold [14]. In this study, we demonstrated that the PLG scaffolds II and III, which are of higher porosity than scaffold I, are able to repair full-thickness osteochondral defects of a critical size with a single material (cultured cell-free model).…”
Section: Discussionmentioning
confidence: 99%
“…It is speculated that an osteochondral defect of a critical size cannot be filled with reparative tissue and has deleterious effects leading to the creation of a large defect in the subchondral bone. Therefore, we have developed a new bioabsorbable scaffold made from a synthetic polymer, poly (DL-lactide-co-glycolide) (PLG) [14]. The PLG scaffold has multiple pores, to which the erupted bone marrow cells can attach, and has the possibility to repair the full-thickness osteochondral defects of a critical size made in a rabbit without using the cultured cells, thus preventing the collapse of the surrounding articular cartilage and subchondral bone.…”
Section: Introductionmentioning
confidence: 99%
“…Degradation by-products has been shown to elicit inflammatory response and decreased pH level [98] Mechanical stiffness can sometimes be undesirable [196] Hydrophobicity [196] [197]; [198]; [199]; [197]; [200]; [201]; [202]; [203]; [204]; [205];;…”
Section: Flexibility In Degradation Ratesmentioning
confidence: 99%